Integrated system of free‐space optical and visible light communication for indoor wireless broadband access. Issue 23 (1st November 2015) - Zheng, Zhong; Liu, Lu; Chen, Te; Hu, Weiwei
Abstract : An integrated system of free‐space optical communication and visible light communication for indoor wireless broadband access is proposed. The proposed system features all‐optical links and high capacity. As a proof of concept, 16‐ and 32‐quadrature amplitude modulation single‐carrier frequency domain equalisation transmissions over equivalent 2 km free‐space, 1 km single‐mode fibre, and 2 m indoor free‐space link are demonstrated. About 300 Mbit/s data rate with bit error rate under the forward error correction limit (3.8 × 10 −3 ) and clear constellation maps are achieved.